2022
DOI: 10.1021/acsami.1c22812
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte Reactivity at the Charged Ni-Rich Cathode Interface and Degradation in Li-Ion Batteries

Abstract: The chemical and electrochemical reactions at the positive electrode–electrolyte interface in Li-ion batteries are hugely influential on cycle life and safety. Ni-rich layered transition metal oxides exhibit higher interfacial reactivity than their lower Ni-content analogues, reacting via mechanisms that are poorly understood. Here, we study the pivotal role of the electrolyte solvent, specifically cyclic ethylene carbonate (EC) and linear ethyl methyl carbonate (EMC), in determining the interfacial reactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
119
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(125 citation statements)
references
References 76 publications
(216 reference statements)
6
119
0
Order By: Relevance
“…Ni-rich, Li-rich materials) and can react in ambient air or in contact with the electrolyte. 19,54,55 The nano-length-scales of the interphases formed at battery electrodes, and their intricate chemical structure are the main reasons why their properties and relations to performance remain so elusive, but also why XPS is commonly the chosen technique to characterise them.…”
Section: An Introduction To Interphases and Practical Considerations ...mentioning
confidence: 99%
“…Ni-rich, Li-rich materials) and can react in ambient air or in contact with the electrolyte. 19,54,55 The nano-length-scales of the interphases formed at battery electrodes, and their intricate chemical structure are the main reasons why their properties and relations to performance remain so elusive, but also why XPS is commonly the chosen technique to characterise them.…”
Section: An Introduction To Interphases and Practical Considerations ...mentioning
confidence: 99%
“…8,77 The understanding that Mn dissolution at high voltages in LNMO is driven by electrolytefacilitated reduction of surface transition metal centers can help us understand the similarities and differences in transition metal dissolution between spinels and layered oxide cathode materials (e.g., NMC) that also have highly reactive surfaces and undergo structural rearrangement during electrochemical cycling. 78,79 During NMC charging, electrolyte oxidation at the particle surface results in a concomitant release of oxygen that results in the production of HF 37,80,81 as well as a reduction of surface transition metals that forms an oxygen-depleted rocksalt layer composed of Ni 2+ , Mn 2+/3+ and Co 2+ . [82][83][84] Thus, in both cathode structures, the surface reconstruction process provides both a source of reduced transition metals and HF needed for metal dissolution, but the extent of dissolution will be highly dependent on the exact composition of the surface layer, which is typically determined by the original stoichiometry of the active material.…”
Section: Mechanistic Understanding Of Transition Metal Dissolution Ce...mentioning
confidence: 99%
“…82,87,88 Preferential Mn dissolution over Ni and Co has been observed in NMC cells and often deviates from what might be expected based on the stoichiometry of the material. [80][81][82]88,89 This preferential Mn dissolution has been attributed to the higher solubility of Mn 2+ in non-aqueous electrolytes compared to Ni and Co 10,81,82 as well as the tendency of surface Ni in Ni-rich NMCs to form a stable NiO rocksalt phase. 88,90 One study on the comparative aging between spinels and layered cathodes showed that LMO/LNMO exhibit at least 3´ more transition metal dissolution compared to NMC-type cathodes during aging, 40,44 but how transition metal dissolution proceeds with different cathodes during electrochemical cycling is still not well understood.…”
Section: Mechanistic Understanding Of Transition Metal Dissolution Ce...mentioning
confidence: 99%
“…Such discrepancies heavily complicate the interpretation of different suggested degradation mechanisms. [29][30][31][32] Thus, it is important to understand overarching degradation patterns that are inherent to Li-and Mn-rich cathodes irrespective of synthesis routes, and under well-controlled characterisation conditions.…”
Section: Introductionmentioning
confidence: 99%